N-nacnac stabilized tetrylenes: access to silicon hydride systems via migration processes - Cao Huan Do, D; Kolychev, EL; Hicks, J; Aldridge, S (Wiley, 2021)
The use of an amino-functionalized β-diketiminate (′N-nacnac′) ligand in low-valent silicon chemistry is investigated. In particular, the use of (LDipp)SiCl (LDipp=HC{(Me2N)CNDipp}2) to generate silicon-containing products via metathesis chemistry is explored, in light of previously reported complications arising from heterocycle ring contraction. In the case of Na[C5H5], chloride metathesis is accompanied not by rearrangement of the N-nacnac ligand, but by a C-to-Si hydrogen migration process, generating the hydridosilicon(IV) species (LDipp)Si(H)(C5H4), which features a silafulvene core. The potential intermediate arising from initial chloride/cyclopentadienide substitution can be modelled by the chemistry of the corresponding Ge(II) and Sn(II) systems, which generate (LDipp)E(η1−C5H5) (E=Ge, Sn) via straightforward metathesis chemistry. A Si(II) hydride species can be generated from (LDipp)SiCl via metathesis by making use of a d-block reagent which can act as both hydride source and coordinative trap for (LDipp)SiH. Thus, the reaction of (LDipp)SiCl with K[(η5−C5H4Me)Mn(CO)2H] leads to the formation of (η5−C5H4Me)Mn(CO)2{Si(H)LDipp} – the first silylene complex containing this half-sandwich manganese fragment.